Long-term predictions of COVID-19 waves in China based on an improved SEIRS-Q model of antibody failure - Mengxuan Lin; Pengyuan Nie; Qunjiao Yan; Xinying Du; Jinquan Chen; Yaqing Jin; Ligui Wang; Lei Wang (Journal of Infection in Developing Countries)
Introduction: China had already experienced two COVID-19 epidemics since the promulgation of 10 new prevention and control measures in December 2022.